PROFILE OF COMMUNITY UNDERSTANDING AND LITERACY ABOUT DISASTER RISK MITIGATION: THE RESPONSES OF JAVA SOUTH COAST COMMUNITY AGAINST MEGATHRUST EARTHQUAKE AND TSUNAMI PREDICTION - Iqbal Ainur Rizki; Handoko Bintoro; Khoirun Nisa'; Prima Rahman; Arie Realita; Utama Alan Deta (Universitas Sebelas Maret (UNS), 2022)
Widiyantoro et al., as Institut Teknologi Bandung (ITB) scientists, predict the worst possibility that in the south of Java Island, a megathrust earthquake with a maximum magnitude of up to 9.1 on the Richter scale and a tsunami of up to 20 meters. So understanding and literacy about mitigation of the megathrust earthquake and tsunami need to be improved so that the South Coast of Java Island (Pansela) community has prepared for these disasters. This study aims to analyze the understanding and literacy of the Pansela community of the earthquake and tsunami disaster against the predictions made by ITB scientists. This study uses a qualitative descriptive method with a total of 57 community respondents living in Pansela. The study results show that most communities believe in this prediction and have fewer mitigation efforts against this disaster. However, the respondents still did not know the specifics of the megathrust earthquake. They considered an earthquake in the south of Java Island related to the megathrust earthquake. Therefore, it is necessary to increase community understanding and literacy regarding mitigation efforts against megathrust earthquakes and tsunami.